2010
DOI: 10.1063/1.3468376
|View full text |Cite
|
Sign up to set email alerts
|

The explanation of barrier height inhomogeneities in Au/n-Si Schottky barrier diodes with organic thin interfacial layer

Abstract: The forward bias current-voltage (I-V) characteristics of Au/n-Si Schottky barrier diodes (SBDs) with Zn doped poly(vinyl alcohol) (PVA:Zn) interfacial layer have been investigated in the wide temperature range of 80–400 K. The conventional Richardson plot of the ln(Io/T2) versus q/kT has two linear regions: the first region (200–400 K) and the second region (80–170 K). The values of activation energy (Ea) and Richardson constant (A∗) were obtained from this plot and especially the values of A∗ are much lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The deviation may be due to the spatially inhomogeneous barriers and potential fluctuations at the interface that consist of low and high barrier areas, that is, the current through the diode will flow preferentially through the lower barriers in the potential distribution. The spatial barrier inhomogeneities in Schottky diodes are described by Gaussian distribution function [31,36,37]. The conventional Richardson plot is modified by Gaussian distribution function as follows [31,37]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deviation may be due to the spatially inhomogeneous barriers and potential fluctuations at the interface that consist of low and high barrier areas, that is, the current through the diode will flow preferentially through the lower barriers in the potential distribution. The spatial barrier inhomogeneities in Schottky diodes are described by Gaussian distribution function [31,36,37]. The conventional Richardson plot is modified by Gaussian distribution function as follows [31,37]:…”
Section: Resultsmentioning
confidence: 99%
“…The spatial barrier inhomogeneities in Schottky diodes are described by Gaussian distribution function [31,36,37]. The conventional Richardson plot is modified by Gaussian distribution function as follows [31,37]:…”
Section: Resultsmentioning
confidence: 99%
“…This leads to Fermi level pinning, thereby reducing its performance drastically and limiting its application to be used as tailor-made devices. However, the presence of an interfacial layer between the metal contact and the semiconductor can lead to change in band alignment by changing the barrier height (BH) [2,[10][11][12][13][14]. This change is related to many parameters such as the type of the chosen organic compound and its formation, its thickness, the process of surface preparation, the impurity concentration of a semiconductor and the interfacial layerinduced dipole at the M-S interface [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The current-voltage characteristic of Au/V 2 O 5 /n-Si SBDs at 145 K is also shown in the inset of figure 2. However, many research groups [6][7][8] have reached up to 80 K using IL of different organic or polymer materials. Again, in order to determine Schottky parameters such as series resistance (R s ), ideality factor and barrier height from the temperature dependent forward bias I-V characteristics we have employed the model of Cheung and Cheung.…”
Section: A Current-voltage Characteristicsmentioning
confidence: 99%
“…Taşçıoglu et.al. 6 reported that organic IL in MS structures improved the Schottky diode properties. A PVA film doped with different concentrations of nickel (Ni) and zinc (Zn) as IL between metal and semiconductor was also reported.…”
Section: Introductionmentioning
confidence: 99%